2005
DOI: 10.1093/nar/gki766
|View full text |Cite
|
Sign up to set email alerts
|

Differential and collaborative actions of Rad51 paralog proteins in cellular response to DNA damage

Abstract: Metazoan Rad51 plays a central role in homologous DNA recombination, and its activity is controlled by a number of Rad51 cofactors. These include five Rad51 paralogs, Rad51B, Rad51C, Rad51D, XRCC2 and XRCC3. We previously hypothesized that all five paralogs participate collaboratively in repair. However, this idea was challenged by the biochemical identification of two independent complexes composed of either Rad51B/C/D/XRCC2 or Rad51C/XRCC3. To investigate if this biochemical finding is matched by genetic int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 48 publications
6
77
0
Order By: Relevance
“…Consistent with this notion, an xrcc3/rad51d double deletion in DT40, involving proteins from both the BCDX2 and RAD51C-XRCC3 complexes, exhibits a greater DNA repair defect than either of the two single deletions (22). In the work reported here, we further define the roles played by the RAD51C-XRCC3 complex.…”
supporting
confidence: 78%
“…Consistent with this notion, an xrcc3/rad51d double deletion in DT40, involving proteins from both the BCDX2 and RAD51C-XRCC3 complexes, exhibits a greater DNA repair defect than either of the two single deletions (22). In the work reported here, we further define the roles played by the RAD51C-XRCC3 complex.…”
supporting
confidence: 78%
“…Mutant cell lines deficient in the Rad51 paralogs and Brca2 have also been generated in chicken B-lymphocyte DT40 cells, all of which exhibited reduced levels of spontaneous and mitomycin C (MMC)-induced SCEs [19][20][21][22]. In all the hamster and chicken Rad51 paralog mutants, the formation of Rad51 nuclear foci is severely impaired following treatment with DNA damaging agents (typically IR and MMC).…”
Section: Introductionmentioning
confidence: 99%
“…Smirado et al (2005) have shown that p53-and rad51d-double defective mouse embryonic fibroblasts are cisplatinsensitive. Yonetani et al (2005) also recently reported that rad51d-deficient chicken DT40 cells are extremely sensitive to cisplatin and that both wild type and rad51d-deficient cells are similarly radioresistant. Their study used p53-defective DT40 cells.…”
Section: Discussionmentioning
confidence: 87%
“…RAD51D is important for both DNA repair and telomere maintenance, and is therefore essential for cell viability. In addition, deletion mutants of rad51 paralogs including rad51d in chicken DT40 cells that harbor a p53 defect are highly sensitive to cisplatin compared with wild type cells (Yonetani et al, 2005). Similarly, Smiraldo et al (2005) reported that double mutants of rad51d and p53 are more sensitive to DNA-damaging agent than p53 single mutants.…”
Section: Introductionmentioning
confidence: 98%